A kind of adhesive for SPC board and preparation method thereof
By optimizing the composition and process of SPC plate glue, especially through vacuum stirring and mixing technology, the problem of bonding and composite of SPC plates and honeycomb plates is solved, and efficient bonding effect and suitable process performance are achieved, meeting the needs of the interior decoration field.
Patent Information
- Application Number
- CN202411680306.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art is difficult to achieve effective bonding between SPC boards and honeycomb boards, and cannot meet the composite bonding requirements in the field of interior decoration.
A glue for SPC plates is provided, including component A and component B. Component A is composed of vegetable oil, polyether polyol, heavy calcium, active calcium, molecular sieve, wetting agent, solvent, catalyst and defoaming agent. By optimizing the proportion and particle size of these components, combined with vacuum stirring and mixing technology, the uniform dispersion of inorganic powder materials is ensured and the adhesive properties of the adhesive are improved.
It realizes effective bonding between SPC board and honeycomb board, provides excellent bonding strength, appropriate viscosity and curing time, meets construction needs in different seasons, and improves the adhesion and mechanical properties of the adhesive.
Smart Images

Figure CN119177107B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, in particular to an adhesive for SPC boards and a preparation method thereof. Background Art
[0002] SPC board, the full name of Stone Plastic Composite, is not a plastic material. It is a formaldehyde-free, mildew-proof, fire-proof and waterproof decorative panel made of raw materials such as calcium powder and resin. SPC is usually compounded with a honeycomb layer to obtain an SPC honeycomb board, which is used in various cabinets in the home and walls of work places with special requirements for strong load-bearing capacity, stability and firmness, and moisture resistance. However, SPC boards are difficult to bond based on their material characteristics. For example, a Chinese patent (publication number CN114672274A) discloses a special structural sealant for SPC boards and a preparation method thereof, which mainly improves the shear strength of the sealant by using a polyether terminated with trimethoxysilylpropylcarbamate; a Chinese patent (publication number CN114763463A) discloses a special floor glue for SPC boards and a preparation method thereof, which specifically uses a hydroxyl-terminated polysiloxane as the main bonding system, and cooperates with inorganic particles to optimize and solve the problem that the surface of the colloid is dry and solidified while the inside is not completely solidified, but it cannot meet the bonding and compounding requirements of SPC boards and honeycomb boards. Summary of the invention
[0003] In order to solve the above problems, the present invention provides an adhesive for SPC boards, which can achieve effective bonding between SPC boards and honeycomb boards and is suitable for the field of interior decoration.
[0004] On the one hand, the present invention provides an adhesive for SPC boards, comprising a component A and a component B, wherein the raw materials for preparing the component A at least comprise, by weight, 30-50 parts of vegetable oil, 3-15 parts of polyether polyol, 30-80 parts of heavy calcium, 5-15 parts of active calcium, 0.1-10 parts of molecular sieves, 0.1-5 parts of wetting agents, 2-8 parts of solvents, 0.01-0.3 parts of catalysts, and 0.01-0.3 parts of defoaming agents; and the component B at least comprises a curing agent.
[0005] As a preferred technical solution, the raw materials for preparing component A include at least 30-50 parts of vegetable oil, 8-12 parts of polyether polyol, 55-65 parts of heavy calcium, 5-15 parts of active calcium, 3-8 parts of molecular sieve, 2-5 parts of wetting agent, 3-8 parts of solvent, 0.05-0.12 parts of catalyst, and 0.05-0.2 parts of defoaming agent, by weight.
[0006] As a preferred technical solution, the vegetable oil is selected from at least one of castor oil, soybean oil, rapeseed oil and sunflower oil, preferably castor oil.
[0007] As a preferred technical solution, the hydroxyl value (mgKOH / g) of the polyether polyol is 200-500, preferably 320-355, and the model is polyether polyol HSH305, which comes from Nantong Fanbo Chemical Co., Ltd.
[0008] As a preferred technical solution, the particle size of the heavy calcium is 800-2500 mesh.
[0009] As a preferred technical solution, the heavy calcium is heavy calcium A or heavy calcium B or heavy calcium C.
[0010] As a preferred technical solution, the heavy calcium A includes heavy calcium 1 and heavy calcium 2, the particle size of heavy calcium 1 is 2000-2500 mesh, the particle size of heavy calcium 2 is 1000-1500 mesh, and the mass ratio of heavy calcium 1 to heavy calcium 2 is (0.5-2):1, preferably 1:1.
[0011] As a preferred technical solution, the heavy calcium B includes heavy calcium 3 and heavy calcium 4, the particle size of heavy calcium 3 is 800-1000 mesh, the particle size of heavy calcium 4 is 1000-1500 mesh, and the mass ratio of heavy calcium 3 to heavy calcium 4 is (0.5-2):1, preferably 1:1.
[0012] As a preferred technical solution, the particle size of the heavy calcium carbonate C is 800-1000 mesh.
[0013] As a preferred technical solution, the particle size of the active calcium is 600-1000 mesh, preferably 800 mesh.
[0014] As a preferred technical solution, the pore size of the molecular sieve is 3A grade.
[0015] As a preferred technical solution, the wetting agent is polyethylene glycol, preferably at least one of polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000, and polyethylene glycol 6000, preferably polyethylene glycol 6000.
[0016] In order to ensure the adhesion of the adhesive on the surface of the SPC board, the hydroxyl source in the optimized system of the present invention is a combination of castor oil and polyether polyol, especially the hydroxyl value of the polyether polyol is controlled to be 200-500 mgKOH / g. Under the coordination of the wetting agent, the curing time after the A component and the B component are mixed is short, and the viscosity is within the range suitable for processing. The prepared adhesive has enhanced wetting on the SPC surface and significantly improved adhesion. Further, by introducing heavy calcium, active calcium and molecular sieves into the reaction system, optimizing the particle size and addition amount control of heavy calcium, active calcium and molecular sieves, and coordinating the catalyst addition amount control, the provided adhesive has excellent SPC board-honeycomb board bonding composite strength and suitable viscosity and curing time, meeting the actual use needs of different seasons in spring, summer, autumn and winter. Specifically, the system of the present invention controls the introduction of 0.05-0.12 parts by weight of catalyst by introducing 3A molecular sieve with heavy calcium A and 600-1000 mesh active calcium, so that the viscosity of the product is 25000-35000 (mPa·s), and the curing time is 1.3-1.6h, which meets the actual construction application needs in summer. By introducing 3A molecular sieve with heavy calcium B and 600-1000 mesh active calcium, the introduction of 0.05-0.12 parts by weight of catalyst is controlled, so that the viscosity of the product is 15000-25000 (mPa·s), and the curing time is 1.7-2.3h, which meets the actual construction application needs in spring and autumn. By introducing 3A molecular sieve with heavy calcium C and 600-1000 mesh active calcium, the introduction of 0.05-0.12 parts by weight of catalyst is controlled, so that the viscosity of the product is 7000-15000 (mPa·s), and the curing time is about 2.5h, which meets the actual construction application needs in winter.
[0017] As a preferred technical solution, the solvent is DBE (dibasic acid ester).
[0018] As a preferred technical solution, the catalyst is selected from at least one of dibutyltin dilaurate, dibutyltin dichloride, dioctyltin dilaurate, dibutyltin diacetate, dibutyltin benzoate, di-n-octyltin dilaurate, and dibutyltin diacetate, preferably dibutyltin dilaurate.
[0019] The adhesive provided by the present invention adopts dibutyltin dilaurate as a catalyst, so that the provided adhesive has excellent strength for bonding SPC boards and honeycomb boards.
[0020] As a preferred technical solution, the defoaming agent is a silicone defoaming agent, preferably SGR1832, Xingrui (Shandong).
[0021] As a preferred technical solution, the curing agent is diisocyanate, preferably MDI, Wanhua WANNATE® PM-130.
[0022] As a preferred technical solution, the mass ratio of component A to component B is 100:(10-30), preferably 100:20.
[0023] Another aspect of the present invention provides a method for preparing an adhesive for an SPC board, comprising at least the following steps:
[0024] S1. Mixing vegetable oil, polyether polyol and defoamer by weight to obtain mixture 1;
[0025] S2, adding heavy calcium, active calcium, molecular sieve and wetting agent to mixture 1 in sequence, and mixing by vacuum stirring to obtain mixture 2;
[0026] S3, adding solvent and catalyst to the mixture, stirring and mixing in vacuum to obtain component A;
[0027] S4. When using, stir and mix component A and component B.
[0028] As a preferred technical solution, the stirring and mixing speed in step S1 is 500-1000 r / min, and the stirring and mixing time is 10-30 min.
[0029] As a preferred technical solution, the speed of vacuum stirring and mixing in step S2 is 1000-1500r / min, the time of vacuum stirring and mixing is 0.5-2h, and the vacuum degree is -0.09kpa / cm 2 .
[0030] As a preferred technical solution, the speed of vacuum stirring and mixing in step S3 is 1000-1500r / min, the time of vacuum stirring and mixing is 1-2h, and the vacuum degree is -0.09kpa / cm 2 .
[0031] The present invention ensures the uniformity of the inorganic powder material in the polymer system and the bonding performance and mechanical performance of the adhesive by mixing vegetable oil, polyether polyol and defoamer first and then adding heavy calcium, active calcium, molecular sieve and wetting agent, and controlling the stirring and mixing under vacuum conditions.
[0032] Beneficial Effects
[0033] 1. The present invention provides an adhesive for SPC boards, which can achieve effective bonding between SPC boards and honeycomb boards and is suitable for the field of interior decoration.
[0034] 2. The hydroxyl source in the optimized system of the present invention is a combination of castor oil and polyether polyol, especially the hydroxyl value of the polyether polyol is controlled to be 200-500 mgKOH / g. Under the cooperation of the wetting agent, the curing time after the A component and the B component are mixed is short, and the viscosity is within the range suitable for processing. The prepared adhesive has enhanced wetting effect on the SPC surface and significantly improved adhesion.
[0035] 3. By introducing heavy calcium, active calcium and molecular sieve into the reaction system, optimizing the particle size and addition amount of heavy calcium, active calcium and molecular sieve, and coordinating the addition amount of catalyst, the provided adhesive has excellent SPC board-honeycomb board bonding composite strength and suitable viscosity and curing time, meeting the actual use needs in different seasons of spring, summer, autumn and winter.
[0036] 4. The adhesive provided by the present invention adopts dibutyltin dilaurate as a catalyst, so that the adhesive provided has excellent strength for bonding SPC boards and honeycomb boards.
[0037] 5. The present invention mixes vegetable oil, polyether polyol and defoamer first, then adds heavy calcium, active calcium, molecular sieve and wetting agent, and controls the stirring and mixing under vacuum conditions to ensure the uniformity of dispersion of inorganic powder materials in the polymer system and the bonding performance and mechanical properties of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a graph showing the bonding strength test results of the SPC board adhesive provided in Example 1 of the present invention used for an SPC board and a honeycomb board.
[0039] Figure 2 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the adhesive provided in Example 2 of the present invention.
[0040] Figure 3 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the adhesive provided in Example 3 of the present invention.
[0041] Figure 4 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 1 of the present invention.
[0042] Figure 5 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 2 of the present invention.
[0043] Figure 6 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 3 of the present invention.
[0044] Figure 7This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 4 of the present invention.
[0045] Figure 8 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 5 of the present invention.
[0046] Fig. 9 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 6 of the present invention.
[0047] Fig.10 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 7 of the present invention.
[0048] Fig.11 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 8 of the present invention.
[0049] Fig.12 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 9 of the present invention.
[0050] Fig.13 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 10 of the present invention.
[0051] Fig.14 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 11 of the present invention.
[0052] Fig.15 This is a graph showing the test results of the bonding strength between the SPC board and the honeycomb board using the SPC board glue provided in Comparative Example 12 of the present invention. DETAILED DESCRIPTION
[0053] The sources of the raw materials in the examples and comparative examples of the present invention are shown in Table 1.
[0054] Table 1
[0055]
[0056] Examples 1-3, Comparative Examples 1-12
[0057] Examples 1-3 and Comparative Examples 1-12 of the present invention provide a glue for SPC boards, and the raw materials for preparing the glue are shown in Table 2 and Table 3.
[0058] Table 2
[0059]
[0060] Table 3
[0061]
[0062] On the other hand, Examples 1-3 and Comparative Examples 1-12 of the present invention provide a method for preparing an adhesive for an SPC board, comprising the following steps:
[0063] S1. Mixing vegetable oil, polyether polyol and defoamer by weight to obtain mixture 1;
[0064] S2, adding heavy calcium, active calcium, molecular sieve and wetting agent to mixture 1 in sequence, and mixing by vacuum stirring to obtain mixture 2;
[0065] S3, adding solvent and catalyst to the mixture, stirring and mixing in vacuum to obtain component A;
[0066] S4. When using, stir and mix component A and component B.
[0067] The stirring and mixing speed in step S1 is 800 r / min, and the stirring and mixing time is 20 min.
[0068] The speed of vacuum stirring and mixing in step S2 is 1200 r / min, the time of vacuum stirring and mixing is 1 h, and the vacuum degree is -0.09 kPa / cm 2 .
[0069] The speed of vacuum stirring and mixing in step S3 is 1300 r / min, the time of vacuum stirring and mixing is 1.5 h, and the vacuum degree is -0.09 kPa / cm 2 .
[0070] Performance Testing
[0071] 1. Apply glue to the surface of the SPC board provided in Examples 1-3 and Comparative Examples 1-12 (the glue application amount in each example is the same, which is 250 g / m 2 ), and then cover the honeycomb board. After placing it at 25℃ for one day, control the hand tearing force (1-5 levels, increasing step by step, refer to Table 5 for the corresponding strength of 1-5 levels) to peel the SPC board and the honeycomb board, observe whether the SPC board can be peeled off from the surface of the honeycomb board and the adhesion area of the glue on the SPC board after peeling (the larger the adhesion area of the glue on the SPC board after peeling, the better the bonding strength, and the result judgment standard is shown in Table 6). Evaluate the bonding strength of the glue used for the SPC board. The results are shown in Tables 4 and Figure 1-15 .
[0072] 2. The viscosity of the SPC board glue provided in Examples 1-3 and Comparative Examples 1-12 was tested using a Brookfield (USA) DV2TLVTJ0 viscometer, 5# rotor, 10 r / min. The test results are shown in Table 4.
[0073] 3. Referring to GB / T 7123.1-2015, the curing time of the SPC board glue provided in Examples 1-3 and Comparative Examples 1-12 was tested. The test results are shown in Table 4.
[0074] Table 4
[0075]
[0076] Table 5
[0077]
[0078] Table 6
[0079]
[0080] Analysis of the above table shows that: the change of the hydroxyl source in Comparative Examples 1 and 2 relative to Example 1 results in a decrease in the bonding strength between the SPC board and the honeycomb board of the product; the molecular sieve in Comparative Example 3 is replaced from 4A grade to 3A grade relative to Example 1, and the bonding strength between the SPC board and the honeycomb board of the product is reduced. The change in the amount of heavy calcium added in Comparative Examples 4 and 5 relative to Example 1 results in a decrease in the bonding strength between the SPC board and the honeycomb board of the product. The change in the particle size combination of heavy calcium in Comparative Examples 6-11 relative to Examples 1-3 results in a decrease in the bonding strength between the SPC board and the honeycomb board of the product. The change in the catalyst in Comparative Example 12 results in a decrease in the bonding strength between the SPC board and the honeycomb board of the product, and an extension of the curing time.
Claims
1. A glue for SPC board, characterized in that: The invention comprises component A and component B. The raw materials for preparing component A include at least 30-50 parts of vegetable oil, 8-12 parts of polyether polyol, 55-65 parts of heavy calcium, 5-15 parts of active calcium, 3-8 parts of molecular sieve, 2-5 parts of wetting agent, 3-8 parts of solvent, 0.05-0.12 parts of catalyst and 0.05-0.2 parts of defoaming agent by weight. Component B includes at least a curing agent. The vegetable oil is castor oil, and the hydroxyl value of the polyether polyol is 200-500. mgKOH / g; the pore size of the molecular sieve is 3A grade; the heavy calcium is heavy calcium A or heavy calcium B or heavy calcium C; the heavy calcium A is a combination of heavy calcium 1 and heavy calcium 2, the particle size of heavy calcium 1 is 2000-2500 mesh, the particle size of heavy calcium 2 is 1000-1500 mesh, and the mass ratio of heavy calcium 1 to heavy calcium 2 is 1:1; the heavy calcium B is a combination of heavy calcium 3 and heavy calcium 4, the particle size of heavy calcium 3 is 800-1000 mesh, the particle size of heavy calcium 4 is 1000-1500 mesh, and the mass ratio of heavy calcium 3 to heavy calcium 4 is 1:1; the particle size of heavy calcium C is 800-1000 mesh; the catalyst is selected from at least one of dibutyltin dilaurate, dibutyltin dichloride, dioctyltin dilaurate, dibutyltin diacetate, dibutyltin benzoate, di-n-octyltin dilaurate, and dibutyltin diacetate.
2. The SPC board glue according to claim 1, characterized in that: The particle size of the active calcium is 600-1000 meshes.
3. The adhesive for SPC board according to claim 1, characterized in that: The wetting agent is polyethylene glycol.
4. The adhesive for SPC board according to claim 3, characterized in that: The polyethylene glycol is selected from at least one of polyethylene glycol 1000, polyethylene glycol 2000, polyethylene glycol 4000 and polyethylene glycol 6000.
5. The adhesive for SPC board according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.
6. The adhesive for SPC board according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.
7. The adhesive for SPC board according to claim 1, characterized in that: The curing agent is diisocyanate.
8. The adhesive for SPC board according to claim 7, characterized in that: The mass ratio of the component A to the component B is 100:(10-30).
9. A method for preparing the adhesive for SPC board according to any one of claims 1 to 8, characterized in that At least the following steps are included: S1. Mixing vegetable oil, polyether polyol and defoamer by weight to obtain mixture 1; S2, adding heavy calcium, active calcium, molecular sieve and wetting agent to mixture 1 in sequence, and mixing by vacuum stirring to obtain mixture 2; S3, adding solvent and catalyst to the mixture, stirring and mixing in vacuum to obtain component A; S4. When using, stir and mix component A and component B.
10. The method for preparing the adhesive for SPC board according to claim 9, characterized in that: The stirring and mixing speed in step S1 is 500-1000 r / min, and the stirring and mixing time is 10-30 min.
Citation Information
Patent Citations
Acrylic acid modified MS sealant and preparation method thereof
CN114672274A
Floor glue special for SPC board and preparation method of floor glue
CN114763463A
Polyurethane adhesive combined polyether for melamine board as well as preparation method and application of polyurethane adhesive combined polyether
CN115975147A
Novel sealant for preventing corrosion of color steel plate and preparation method thereof
CN115975570A